KELAYAKAN USAHA BUDIDAYA IKAN NILA “AKI DALANG” DI KECAMATAN JANGKANG, KABUPATEN SANGGAU - Dewi Kurniati; Eggi Anugriansyah; Erlinda Yurisinthae (JURNAL BORNEO AKCAYA, 2022)
Freshwater fish that are of interest to the general public are tilapia. They have a relatively high protein, consisting of 55,58% wet protein and 15,41% dry protein. It makes tilapia one of the potential fish to be cultivated and can be an income source. Therefore, it is necessary to do the feasibility study on tilapia cultivation. This study aims to analyze the feasibility of tilapia cultivation (a case study of Aki Dalang's tilapia farming business in Jangkang District, Sanggau Regency). The research was conducted at the Aki Dalang business in Sape Village, Jangkang District, Sanggau Regency, involving four respondents from Aki Dalang's business and three from outside Aki Dalang's business. The collected data were analyzed using the R/C Ratio and B/C Ratio. The results showed that the Aki Dalang tilapia cultivation business was feasible to develop because the R/C Ratio showed > 1, i.e. R/C > 6.04. And the Aki Dalang tilapia cultivation business is profitable to develop because the B/C Ratio shows > 1, namely the B/C Ratio of 5.04. It is recommended that the government issue a policy in assisting waterwheel technology to improve the pond water quality for seed-stocking increase.